DILEMA ETIKA DALAM PENGAMBILAN KEPUTUSAN MILITER: MENGGALI INTERAKSI ANTARA ETIKA PERANG DAN HUKUM HUMANITER - Alexander CW; Fachrudi H, Tarsisius Susilo, M.Asep Apandi, S.Dhani Broto (JOURNAL OF LAW AND NATION, 2025)
This article examines the relationship between ethical principles and humanitarian law in the context of warfare. Military forces often face dilemmas between carrying out effective actions and maintaining ethical standards that protect human rights. Through an analysis of various incidents and moral challenges encountered in the field, this article aims to understand how decisions made by military personnel can affect the application of law and its impact on morality. The study also highlights the importance of ethics training within the military, which plays a significant role in preventing violations of humanitarian law during armed conflict. By exploring the dynamics between ethics and humanitarian law, this article offers insights on how preventive mechanisms and international regulations can strengthen the implementation of law and reduce violations that occur on the battlefield.